Technology Induced Productivity in Fisheries - Gopal, Nikita; Menon, Sreevalsan J.; V., Annamalai (Fishery Technology, 2025)
Artisanal fisheries in Cochin are characterised by the presence of three types of craft operations (large motorised crafts, small motorised crafts and non-motorised crafts) representing three different technological gradations. The study investigated the technological gradations vis-a-vis capital and labour productivity. It was observed that more sophisticated the technology, higher are the costs as well as gross returns. Though every increase in capital was accompanied by an increase in labour, capital increase per labour was not proportionate, i.e. increase in capital is more than increase in labour, showing a labour saving character in the process of technological sophistication. In terms of productivity, capital productivity declines as capital intensity increases. Optimum use of capital in terms of productivity does not occur in fish harvest technologies.